Intrathecal morphine in lumbar spine surgery: a novel injection technique. (3rd June 2015) - Jewett, GA; Yavin, D; Dhaliwal, P; Whittaker, T; Krupa, J; Du Plessis, S
Abstract : Background: Intrathecal morphine (ITM) is an efficacious method of providing post-operative analgesia. Despite adoption in many surgical fields, ITM has yet to become a standard of care in lumbar spine surgery. This may in part be attributed to concerns over precipitating a cerebrospinal fluid (CSF) leak following dural puncture. Methods: The dural sac is penetrated obliquely at a 30° angle to prevent overlap of dural and arachnoid puncture sites. Oblique injection in instances of limited dural exposure is made possible by introducing a 60° bend to a standard 30-gauge needle. Participating spinal surgeons were provided with brief instructions outlining the injection technique. Adherence and complications were collected prospectively. Results: The technique was applied to 98 cases of elective lumbar fusion at our institution. Two cases (2.0%) of non-adherence followed pre-injection dural tear. 96 cases of oblique ITM injection resulted in no attributable instances of post-operative CSF leakage. Two cases (2.1%) of transient, self-limited CSF leakage immediately following ITM injection were observed without associated sequelae or requirement for further intervention. Conclusions: Oblique dural puncture is not associated with increased incidence of post-operative CSF leakage. This safe and reliable method of delivery of ITM should be routinely considered in lumbar spine surgery.